Polylactic acid fiber with controllable degradation period, preparation method of polylactic acid fiber and application of polylactic acid fiber as medical suture
By adopting polylactic fibers with a skin core structure and setting up an uncapped polylactic acid surface coating outside the cortex, the problem of slow degradation rate of PLA fibers is solved, biocompatibility and biosafety are achieved, and the degradation cycle is controlled, which is suitable for medical sutures.
Patent Information
- Application Number
- CN202510046031.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-10
- Publication Date
- 2025-04-15
AI Technical Summary
The degradation rate of existing PLA fibers is slow and cannot meet the short-term degradation requirements of some medical sutures. At the same time, the modification process is complex, which may affect the biocompatibility and safety of the fibers.
The polylactic acid fiber adopts a skin-core structure, the core layer is a low molecular weight first polylactic acid, the cortex is a high molecular weight second polylactic acid, and an uncapped polylactic acid surface coating is provided outside the cortex, and the degradation period is adjusted by molecular weight and mass ratio.
The biocompatibility and biosafety of polylactic fibers are achieved. At the same time, by adjusting the molecular weight and mass ratio of the cortex and core layers, the fiber degradation cycle can be controlled and adapted to different medical needs.
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of medical fiber materials, and in particular relates to a polylactic acid fiber with a controllable degradation cycle, a preparation method thereof, and an application of the fiber as a medical suture. Background Art
[0002] Surgical sutures refer to a special type of thread used for wound ligation, hemostasis and tissue suture during surgical operations. According to their biodegradability, they can be divided into two categories: non-absorbable and absorbable. Among them, absorbable sutures include natural fiber and synthetic polymer sutures.
[0003] Polylactic acid (PLA) is a green and environmentally friendly degradable polymer material. Due to its good biocompatibility and biodegradability, PLA is widely used in the biomedical field, and degradable medical sutures are one of its applications. However, the degradation rate of PLA fibers is slow and cannot meet the requirements of some medical sutures for degradation in a short period of time. Therefore, improving the degradation rate of PLA fibers through modification is the key to the promotion and application of PLA medical sutures.
[0004] The Chinese patent application number CN201510492526.0 discloses an absorbable medical suture with good mechanical properties, and its raw materials include by weight: 100-120 parts of modified PLA, 20-40 parts of polyglycolide, 4-6 parts of sorbitol, 3-5 parts of methacrylic acid, and 5-6 parts of cinnamon oil. Among them, the preparation method of modified PLA is: mixing modified chitosan, polyethylene glycol, stannous chloride, and lactide, heating, stirring and purifying, and drying to obtain modified PLA. This method uses chitosan to shorten the degradation cycle of PLA, and PLA extends the degradation cycle of chitosan. The two interact with each other to make the modified PLA have a suitable degradation cycle.
[0005] A Chinese patent application numbered CN201510492506.3 discloses a method for preparing an absorbable medical suture. Modified polylactic acid, epoxy soybean oil, genipin, and castor oil are mixed and prepared by a melt spinning method to obtain an absorbable medical suture. The modified polylactic acid contains a chitosan component, and chitosan is also used to reduce the degradation cycle of PLA.
[0006] The Chinese patent application number 201510638519.7 discloses a polylactic acid-polyvinyl alcohol type medical absorbable suture and its preparation method. The suture includes the following components: 40-60 parts of polylactic acid-polyvinyl alcohol, 10-15 parts of collagen, 1-3 parts of glycerol, 3-5 parts of chitosan, 3-5 parts of cross-linking agent, 2-4 parts of stabilizer and 1-3 parts of antibacterial agent; the preparation method of the suture is: adding each component to the reactor by weight, heating and stirring to obtain a blend; the blend is extruded, water-cooled, air-dried, and pelletized to obtain a masterbatch: the masterbatch is heated to melt, degassing and darkening to form primary fibers, and the primary fibers are stretched twice in a water bath to obtain the suture. The medical suture prepared by this method can be completely absorbed in the body within 15 to 22 days.
[0007] It can be seen from the above that the existing modification methods for PLA fibers have a long modification process and complex technology on the one hand, and introduce more modified substances on the other hand, which to a certain extent destroys the mechanical properties and biosafety of PLA. Summary of the invention
[0008] In view of this, the technical problem to be solved by the present invention is to provide a polylactic acid fiber with high biocompatibility and biosafety and a simple process flow and a controllable degradation cycle, a preparation method thereof and an application thereof as a medical suture.
[0009] The present invention provides a polylactic acid fiber with a controllable degradation cycle, wherein the polylactic acid fiber comprises a core layer and a skin layer wrapped outside the core layer; the core layer is a first polylactic acid; the skin layer is a second polylactic acid; the weight average molecular weight of the first polylactic acid is 20,000 to 50,000; the weight average molecular weight of the second polylactic acid is 100,000 to 200,000.
[0010] Preferably, the mass ratio of the skin layer to the core layer is 5:5 to 9:1.
[0011] Preferably, a surface coating is further provided outside the skin layer; the surface coating comprises a third polylactic acid and a lubricant; and the third polylactic acid is an uncapped polylactic acid.
[0012] Preferably, the weight average molecular weight of the third polylactic acid is 5000 to 15000;
[0013] and / or, the lubricant is selected from stearic acid and / or calcium stearate;
[0014] And / or, the mass ratio of the third polylactic acid to the lubricant is 5:5 to 8:2.
[0015] Preferably, the thickness of the surface coating is 0.5-1 μm.
[0016] Preferably, the tensile strength of the polylactic acid fiber is 2.6 to 4.5 cN / dtex;
[0017] And / or, the degradation period of the polylactic acid fiber is 15 to 90 days.
[0018] The present invention also provides a method for preparing the above-mentioned polylactic acid fiber, comprising the following steps:
[0019] S1) melting the first polylactic acid and the second polylactic acid respectively to obtain a first polylactic acid melt and a second polylactic acid melt;
[0020] S2) performing core-skin composite spinning of the first polylactic acid melt and the second polylactic acid melt to obtain raw yarn;
[0021] S3) pulling the raw silk to obtain polylactic acid fiber.
[0022] Preferably, the melting temperature in step S1) is 200°C to 240°C;
[0023] The temperature of the sheath-core composite spinning in step S2) is 190° C. to 240° C.;
[0024] The multiple of the pulling in step S3) is 1 to 5; the pulling temperature is 100° C. to 130° C.
[0025] Preferably, after the pulling in step S3), surface coating is further performed to form a surface coating to obtain polylactic acid fibers;
[0026] The coating solution used for the surface coating comprises a third polylactic acid, a lubricant and an organic solvent; the third polylactic acid is an uncapped polylactic acid.
[0027] The present invention also provides an application of the polylactic acid fiber as a medical suture.
[0028] The present invention provides a polylactic acid fiber with a controllable degradation cycle, the polylactic acid fiber comprising a core layer and a skin layer wrapped outside the core layer; the core layer is a first polylactic acid; the skin layer is a second polylactic acid; the weight average molecular weight of the first polylactic acid is 20,000 to 50,000; the weight average molecular weight of the second polylactic acid is 100,000 to 200,000. Compared with the prior art, the polylactic acid fiber provided by the present invention has a skin-core structure, the skin layer is a high molecular weight polylactic acid, and the core layer is a low molecular weight polylactic acid, so that the main component of the polylactic acid fiber is mainly polylactic acid, and no other organic molecules are introduced, thereby ensuring the biocompatibility and biosafety of the polylactic acid fiber; at the same time, the degradation cycle can be adjusted by the change of the molecular weight of the skin layer and the core layer and the mass ratio.
[0029] Furthermore, the degradation cycle is further adjusted by providing a surface coating comprising uncapped polylactic acid outside the skin layer. DETAILED DESCRIPTION
[0030] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0031] The present invention provides a polylactic acid fiber with a controllable degradation cycle, wherein the polylactic acid fiber comprises a core layer and a skin layer wrapped outside the core layer; the core layer is a first polylactic acid; the skin layer is a second polylactic acid; the weight average molecular weight of the first polylactic acid is 20,000 to 50,000; the weight average molecular weight of the second polylactic acid is 100,000 to 200,000.
[0032] In some embodiments provided by the present invention, the weight average molecular weight of the first polylactic acid is specifically 20,000, 50,000 or 40,000.
[0033] According to the present invention, the first polylactic acid may be end-capped or unend-capped, without any special limitation; in a specific embodiment provided by the present invention, the first polylactic acid is preferably unend-capped polylactic acid.
[0034] In some embodiments provided by the present invention, the weight average molecular weight of the second polylactic acid is specifically 100,000, 200,000 or 160,000.
[0035] According to the present invention, the second polylactic acid may be end-capped or unend-capped, without any special limitation; in a specific embodiment provided by the present invention, the second polylactic acid is preferably end-capped polylactic acid, more preferably acylated end-capped polylactic acid.
[0036] According to the present invention, the mass ratio of the skin layer to the core layer is preferably 5:5 to 9:1; in a specific embodiment provided by the present invention, the mass ratio of the skin layer to the core layer is specifically 5:5, 7:3, 9:1 or 6:4.
[0037] According to the present invention, a surface coating is preferably provided outside the cortex; the thickness of the surface coating is preferably 0.5 to 1 μm; the surface coating preferably includes a third polylactic acid and a lubricant; the third polylactic acid is preferably an uncapped polylactic acid; the weight average molecular weight of the third polylactic acid is preferably 5000 to 15000; in some embodiments provided by the present invention, the weight average molecular weight of the third polylactic acid is specifically 5000, 8000, 15000, 10000 or 12000; the lubricant can be a lubricant well known to those skilled in the art without any special restrictions, and is preferably stearic acid and / or calcium stearate in the present invention; the mass ratio of the third polylactic acid to the lubricant is preferably 5:5 to 8:2; optionally, the mass ratio of the third polylactic acid to the lubricant is 5:5, 6:4, 6.67:3.33, 7:3, 7.5:2.5, 8:2 or a range between any two of the above values.
[0038] According to the present invention, the tensile strength of the polylactic acid fiber is preferably 2.6 to 4.5 cN / dtex.
[0039] According to the present invention, the degradation period of the polylactic acid fiber is preferably 15 to 90 days.
[0040] The polylactic acid fiber provided by the present invention has a skin-core structure, wherein the skin layer is high molecular weight polylactic acid and the core layer is low molecular weight polylactic acid, so that the main component of the polylactic acid fiber is mainly polylactic acid, and no other organic molecules are introduced, thereby ensuring the biocompatibility and biosafety of the polylactic acid fiber; at the same time, the degradation cycle can be adjusted by the change of the molecular weight and mass ratio of the skin layer and the core layer. Furthermore, the degradation cycle can be further adjusted by arranging a surface coating containing uncapped polylactic acid outside the skin layer.
[0041] The present invention also provides a method for preparing the above-mentioned polylactic acid fiber, comprising the following steps: S1) melting the first polylactic acid and the second polylactic acid respectively to obtain a first polylactic acid melt and a second polylactic acid melt; S2) performing sheath-core composite spinning on the first polylactic acid melt and the second polylactic acid melt to obtain a raw yarn; S3) pulling the raw yarn to obtain polylactic acid fiber.
[0042] The present invention has no particular limitation on the sources of all raw materials, and any raw materials available on the market can be used.
[0043] The first polylactic acid and the second polylactic acid are melted separately to obtain a first polylactic acid melt and a second polylactic acid melt; the first polylactic acid and the second polylactic acid are the same as described above and will not be repeated here; the mass ratio of the second polylactic acid to the first polylactic acid is preferably 5:5-9:1; in a specific embodiment provided by the present invention, the mass ratio of the second polylactic acid to the first polylactic acid is specifically 5:5, 7:3, 9:1 or 6:4; the melting temperature is preferably 200°C-240°C; in the present invention, specifically, the melting temperature of the first polylactic acid is preferably 200°C-220°C, more preferably 200°C-210°C; the melting temperature of the second polylactic acid is preferably 230°C-240°C; the first polylactic acid and the second polylactic acid are preferably melted in a twin-screw extruder.
[0044] The first polylactic acid melt and the second polylactic acid melt are subjected to sheath-core composite spinning to obtain raw yarn; the temperature of the sheath-core composite spinning is preferably 190°C to 240°C; in some embodiments provided by the present invention, the temperature of the sheath-core composite spinning is specifically 190°C, 220°C, 240°C or 230°C; in the present invention, the sheath-core composite spinning is specifically: the first polylactic acid melt and the second polylactic acid melt are passed through the same-plate sheath-core composite spinning component, and ejected from the sheath-core composite spinneret to obtain raw yarn; the same The temperature of the core-skin type composite spinning component is preferably 190°C to 240°C; in some embodiments provided by the present invention, the temperature of the core-skin type composite spinning component is specifically 190°C, 220°C, 240°C or 230°C; the diameter of the precursor is preferably 10 to 100μm; optionally, the diameter of the precursor is 10μm, 20μm, 30μm, 40μm, 50μm, 60μm, 70μm, 80μm, 90μm, 100μm or a range between any two of the above values.
[0045] The raw silk is pulled; the pulling multiple is preferably 1 to 5; in some embodiments provided by the present invention, the pulling multiple is specifically 1, 3, 5 or 4; the pulling temperature is preferably 100°C to 130°C; in some embodiments provided by the present invention, the pulling temperature is specifically 100°C, 110°C, 120°C or 115°C; after pulling, a skin-core structure polylactic acid fiber is obtained.
[0046] According to the present invention, after traction, surface coating is preferably performed to form a surface coating to obtain polylactic acid fibers; the coating solution used for the surface coating preferably includes a third polylactic acid, a lubricant and an organic solvent; the third polylactic acid is an uncapped polylactic acid; the third polylactic acid and the lubricant are the same as described above and are not repeated here; the organic solvent is an organic solvent well known to those skilled in the art and is not particularly limited. In the present invention, ethyl acetate is preferably used; the third polylactic acid is preferably 5% to 15% of the mass of the coating solution; optionally, the mass of the third polylactic acid is 5%, 8%, 10%, 12%, 15% of the mass of the coating solution or a range between any two of the above values; in the present invention, the coating solution The liquid is preferably prepared according to the following method: mixing the third polylactic acid, a lubricant and an organic solvent to obtain a coating solution, more preferably first adding the third polylactic acid to an organic solvent and then adding the lubricant to mix to obtain a coating solution; the mixing temperature is preferably 40°C to 50°C; in some embodiments provided by the present invention, the mixing temperature is specifically 40°C, 45°C, 50°C or 48°C; after surface coating, drying can form a surface coating to obtain polylactic acid fiber; the thickness of the surface coating is preferably 0.5 to 1 μm; optionally, the thickness of the surface coating is 0.5 μm, 0.6 μm, 0.7 μm, 0.8 μm, 0.9 μm, 1 μm or a range between any two of the above values.
[0047] The present invention also provides an application of the polylactic acid fiber as a medical suture.
[0048] The present invention processes high molecular weight PLA and low molecular weight PLA into skin-core structure fiber, and then coats the outer layer with uncapped low molecular weight PLA, and regulates the degradation cycle of PLA fiber by the molecular weight of PLA used and the weight ratio of PLA in the skin layer and core layer, and the preparation process is simple, the production cost is low, and it has industrial application prospects. On the other hand, in addition to a small amount of calcium stearate component (coating layer) in PLA suture fiber, no other components are added during the modification process, and the main component of PLA in the suture fiber is retained, ensuring the biocompatibility and biosafety of polylactic acid fiber.
[0049] In order to further illustrate the present invention, a polylactic acid fiber with controllable degradation cycle, a preparation method thereof and an application thereof as a medical suture provided by the present invention are described in detail below in conjunction with embodiments.
[0050] The reagents used in the following examples are all commercially available.
[0051] Example 1
[0052] The uncapped PLA with a weight average molecular weight of 20,000 was used as the core layer, and the acylated capped PLA with a weight average molecular weight of 100,000 was used as the skin layer, and the mass ratio of the skin layer to the core layer was 5:5. The skin layer PLA and the core layer PLA were added to the twin-screw extruder respectively and melted at 200°C and 230°C respectively. Then the mixed molten fluid material of the skin layer and the core layer passed through the same-plate skin-core composite spinning assembly at 190°C, and was ejected from the skin-core composite spinneret hole (aperture 0.5mm) to obtain the raw silk. Then the raw silk was stretched 1 times, and the stretching temperature range was 100°C to obtain the skin-core structure PLA fiber. Finally, uncapped PLA with a weight-average molecular weight of 5000 was added to ethyl acetate and stirred, and then calcium stearate powder (the mass ratio of calcium stearate, PLA and ethyl acetate was 1:1:8) was added and stirred, and the temperature was raised to 40°C to obtain a coating solution; then the coating solution was used to coat the skin-core structure PLA fiber (thickness of 0.7 μm) and dried to obtain polylactic acid fiber with a controllable degradation cycle.
[0053] According to the GB / T 14337-2022 test method for tensile properties of chemical fiber staple fibers, the polylactic acid fiber with controllable degradation cycle obtained in Example 1 was tested, and the results showed that the single fiber tensile strength of the polylactic acid fiber with controllable degradation cycle was 2.6 cN / dtex, and the degradation cycle was 15 days.
[0054] Example 2
[0055] The uncapped PLA with a weight average molecular weight of 20,000 was used as the core layer, and the acylated capped PLA with a weight average molecular weight of 200,000 was used as the skin layer. The mass ratio of the skin layer to the core layer was 7:3. The skin layer PLA and the core layer PLA were added to the twin-screw extruder respectively and melted at 200°C and 240°C respectively. Then the mixed molten fluid material of the skin layer and the core layer passed through the same-plate skin-core composite spinning assembly at 220°C, and was ejected from the skin-core composite spinneret hole (aperture 0.5mm) to obtain the raw silk. Then the raw silk was stretched 3 times, and the stretching temperature range was 110°C to obtain the skin-core structure PLA fiber. Finally, uncapped PLA with a weight-average molecular weight of 8000 was added to ethyl acetate and stirred, and then calcium stearate powder was added (the mass ratio of calcium stearate, PLA and ethyl acetate was 0.5:0.5:9) and stirred, and the temperature was raised to 45°C to obtain a coating solution; then the coating solution was used to coat the skin-core structure PLA fiber (thickness of 0.5 μm) and dried to obtain polylactic acid fiber with a controllable degradation cycle.
[0056] According to the GB / T 14337-2022 test method for tensile properties of chemical fiber staple fibers, the polylactic acid fiber with controllable degradation cycle obtained in Example 2 was tested, and the results showed that the single fiber tensile strength of the polylactic acid fiber with controllable degradation cycle was 3.5 cN / dtex, and the degradation cycle was 48 days.
[0057] Example 3
[0058] The uncapped PLA with a weight average molecular weight of 50,000 was used as the core layer, and the acylated capped PLA with a weight average molecular weight of 200,000 was used as the skin layer, and the mass ratio of the skin layer to the core layer was 5:5. The skin layer PLA and the core layer PLA were added to the twin-screw extruder respectively and melted at 210°C and 240°C respectively. Then the mixed molten fluid material of the skin layer and the core layer passed through the same-plate skin-core composite spinning assembly at 240°C, and was ejected from the skin-core composite spinneret hole (aperture 0.5mm) to obtain the raw silk. Then the raw silk was stretched 5 times, and the stretching temperature range was 120°C to obtain the skin-core structure PLA fiber. Finally, uncapped PLA with a weight-average molecular weight of 15,000 was added to ethyl acetate and stirred, and then calcium stearate powder was added (the mass ratio of calcium stearate, PLA and ethyl acetate was 0.5:1.5:8) and stirred, and the temperature was raised to 50°C to obtain a coating solution; the coating solution was then used to coat the skin-core structure PLA fiber (thickness of 1 μm) and dried to obtain polylactic acid fiber with a controllable degradation cycle.
[0059] According to the GB / T 14337-2022 test method for tensile properties of chemical fiber staple fibers, the polylactic acid fiber with controllable degradation cycle obtained in Example 3 was tested, and the results showed that the single fiber tensile strength of the polylactic acid fiber with controllable degradation cycle was 4.5 cN / dtex, and the degradation cycle was 90 days.
[0060] Example 4
[0061] The uncapped PLA with a weight average molecular weight of 50,000 was used as the core layer, and the acylated capped PLA with a weight average molecular weight of 200,000 was used as the skin layer. The mass ratio of the skin layer to the core layer was 9:1. The skin layer PLA and the core layer PLA were added to the twin-screw extruder respectively and melted at 210°C and 240°C respectively. Then the mixed molten fluid material of the skin layer and the core layer passed through the same-plate skin-core composite spinning assembly at 230°C, and was ejected from the skin-core composite spinneret hole (aperture 0.5mm) to obtain the raw silk. Then the raw silk was stretched 5 times, and the stretching temperature range was 120°C to obtain the skin-core structure PLA fiber. Finally, uncapped PLA with a weight-average molecular weight of 10,000 was added to ethyl acetate and stirred, and then calcium stearate powder (the mass ratio of calcium stearate, PLA and ethyl acetate was 0.5:1:9) was added and stirred, and the temperature was raised to 48°C to obtain a coating solution; the coating solution was then used to coat the skin-core structure PLA fiber (thickness of 0.8 μm) and dried to obtain polylactic acid fiber with a controllable degradation cycle.
[0062] According to the GB / T 14337-2022 test method for tensile properties of chemical fiber staple fibers, the polylactic acid fiber with controllable degradation cycle obtained in Example 4 was tested, and the results showed that the single fiber tensile strength of the polylactic acid fiber with controllable degradation cycle was 3.9 cN / dtex, and the degradation cycle was 76 days.
[0063] Example 5
[0064] The uncapped PLA with a weight average molecular weight of 40,000 was used as the core layer, and the acylated capped PLA with a weight average molecular weight of 160,000 was used as the skin layer, and the mass ratio of the skin layer to the core layer was 6:4. The skin layer PLA and the core layer PLA were added to the twin-screw extruder respectively and melted at 210°C and 230°C respectively. Then the mixed molten fluid material of the skin layer and the core layer passed through the same-plate skin-core composite spinning assembly at 220°C, and was ejected from the skin-core composite spinneret hole (aperture 0.5mm) to obtain the raw silk. Then the raw silk was stretched 4 times, and the stretching temperature range was 115°C to obtain the skin-core structure PLA fiber. Finally, uncapped PLA with a weight-average molecular weight of 12,000 was added to ethyl acetate and stirred, and then calcium stearate powder (the mass ratio of calcium stearate, PLA and ethyl acetate was 1:1:8) was added and stirred, and the temperature was raised to 48°C to obtain a coating solution; the coating solution was then used to coat the skin-core structure PLA fiber (thickness of 0.75 μm) and dried to obtain polylactic acid fiber with a controllable degradation cycle.
[0065] According to the GB / T 14337-2022 test method for tensile properties of chemical fiber staple fibers, the polylactic acid fiber with controllable degradation cycle obtained in Example 5 was tested, and the single fiber tensile strength of the polylactic acid fiber with controllable degradation cycle was 4.3 cN / dtex, and the degradation cycle was 59 days.
[0066] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A polylactic acid fiber with controllable degradation cycle, characterized in that: The polylactic acid fiber includes a core layer and a skin layer wrapped outside the core layer; the core layer is a first polylactic acid; the skin layer is a second polylactic acid; the weight average molecular weight of the first polylactic acid is 20,000 to 50,000; the weight average molecular weight of the second polylactic acid is 100,000 to 200,000.
2. The polylactic acid fiber according to claim 1, characterized in that: The mass ratio of the skin layer to the core layer is 5:5 to 9:
1.
3. The polylactic acid fiber according to claim 1, characterized in that: A surface coating is also arranged outside the skin layer; the surface coating comprises a third polylactic acid and a lubricant; and the third polylactic acid is an uncapped polylactic acid.
4. The polylactic acid fiber according to claim 3, characterized in that: The weight average molecular weight of the third polylactic acid is 5000 to 15000; and / or, the lubricant is selected from stearic acid and / or calcium stearate; And / or, the mass ratio of the third polylactic acid to the lubricant is 5:5 to 8:
2.
5. The polylactic acid fiber according to claim 3, characterized in that: The thickness of the surface coating is 0.5-1 μm.
6. The polylactic acid fiber according to claim 3, characterized in that: The tensile strength of the polylactic acid fiber is 2.6 to 4.5 cN / dtex; And / or, the degradation period of the polylactic acid fiber is 15 to 90 days.
7. A method for preparing the polylactic acid fiber according to claim 1, characterized in that: The following steps are involved: S1) melting the first polylactic acid and the second polylactic acid respectively to obtain a first polylactic acid melt and a second polylactic acid melt; S2) performing core-skin composite spinning of the first polylactic acid melt and the second polylactic acid melt to obtain raw yarn; S3) pulling the raw silk to obtain polylactic acid fiber.
8. The preparation method according to claim 7, characterized in that: The melting temperature in step S1) is 200°C to 240°C; The temperature of the sheath-core composite spinning in step S2) is 190° C. to 240° C.; The multiple of the pulling in step S3) is 1 to 5; the pulling temperature is 100° C. to 130° C.
9. The preparation method according to claim 7, characterized in that: After the traction in step S3), the surface is coated to form a surface coating to obtain polylactic acid fibers; The coating solution used for the surface coating comprises a third polylactic acid, a lubricant and an organic solvent; The third polylactic acid is uncapped polylactic acid.
10. Use of the polylactic acid fiber according to any one of claims 1 to 6 or the polylactic acid fiber prepared by the preparation method according to any one of claims 7 to 9 as medical sutures.
Citation Information
Patent Citations
Absorbable medical suture line with good mechanical performance
CN105079869A
Method for preparing absorbable medical sutures
CN105088408A
Polylactic acid-polyvinyl alcohol absorbable surgical suture and preparation method thereof
CN105233332A
Cited By
Barbed surgical suture with radiography function and preparation method thereof
CN120625237A
A barbed surgical suture with radiopaque features and method of making
CN120625237B
Gradient degradation composite absorbable suture line and preparation process
CN121313911A